Coping with stress of mothers of children with disorders belonging toautism spectrum - Świerczyńska, Justyna; Pawłowska, Beata (Current Problems of Psychiatry, 2022)
Introduction. The aim of this study was to analyze the relationship between coping styles in mothers of children with an autism spectrum disorder (ASD) and the severity of their children's symptoms.Material and method. The study included a group of 70 women raising children with a medical diagnosis of ASD. The children with the aforementioned pervasive developmental disorders were from 5 to 16 years old and were patients of the Mental Health Centre in Kielce, Poland. A study involved: our own survey; the Strengths and Difficulties Questionnaire (SDQ) by R. Goodman; the Coping Inventory for Stressful Situations (CISS) questionnaire by Endler and Parker; the Sense of Coherence Scale SOC-29 by Antonovsky; the Set of Questionnaires for the Diagnosis of Autism Spectrum Disorders (ASRS) by S. Goldstein and J. A. Naglieri.Results. The mothers’ preference for emotion-focused and avoidance coping styles was found to correlate significantly with their low sense of coherence and the severity of their child's ASD symptoms measured with ASRS and SDQ.Conclusions:• Emotion-focused and avoidance coping styles were associated with a low sense of coherence in the surveyed women.• The mothers' preference for emotion-focused and avoidance coping styles was associated with increased ASD symptoms, more severe emotional and behavioral deficits and poorer peer interactions in their children.• The mothers' preference for problem-focused coping correlated with a low severity of their children's social and communication deficits.